Investigating Software Piracy in Jordan: An Extension of the Theory of Reasoned Action - Aleassa, Hassan (Journal of business ethics, 2011)
Software piracy, the illegal and unauthorized duplication, sale, or distribution of software, is a widespread and costly phenomenon. According to Business Software Alliance (2008), over 41% of the PC software packages installed worldwide were unauthorized copies. Software piracy behavior has been investigated for more than 30 years. However, after a review of the relevant literature, there appears to be two voids in this literature: a lack of studies in non-Western countries and a scarcity of process studies. This study contributes to literature by developing a software piracy model to better understand the decision-making process that underlies this unethical behavior. The model was tested using data collected from a sample of 323 undergraduate business students. Consistent with the Theory of Reasoned Action (TRA), attitudes toward software piracy and subjective norms were significant predictors of intention to pirate software. Also, the results suggested that ethical ideology, public self-consciousness, and low self-control moderated the effect of these variables on intention to pirate software. The results have important practical implications for the software industry and governments hoping to curtail software piracy. Limitations of the study and recommendations for future studies are discussed as well.